2006
DOI: 10.2141/jpsa.43.250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shrimp Meal on Growth Performance and Digestibility in Growing Broilers

Abstract: In order to use shrimp meal (SM) made from headless black tiger shrimp waste as a protein source for poultry diets, chemical composition of SM and growth performance, dry matter (DM) digestibility and nitrogen (N) retention in broilers given diets containing SM ranged from *ῌ to +0ῌ were measured. Comparing with the data in the previous reports, SM used in the present study was rich in fiber and ash, hence poor in CP. Amino acid profiles revealed that SM had lower concentration of methionineῌcysteine, lysine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 11 publications
3
18
1
4
Order By: Relevance
“…Shrimp meal (SM) has been tried to use as an alternative protein source in chicken diets, while the performances in chickens given SM are not consistent among the reports (Rosenfeld et al, 1997;Gernat, 2001;Khempaka et al, 2006a). Such inconsistency can be explained in part, by the differences in quality of SM originating from different shrimp species (Ngoan et al, 2000), and portion (Meyers, 1986).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shrimp meal (SM) has been tried to use as an alternative protein source in chicken diets, while the performances in chickens given SM are not consistent among the reports (Rosenfeld et al, 1997;Gernat, 2001;Khempaka et al, 2006a). Such inconsistency can be explained in part, by the differences in quality of SM originating from different shrimp species (Ngoan et al, 2000), and portion (Meyers, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, we measured nutritional values and in vitro digestibilities of different SM, such as heads and hulls of white leg (Litopenaeus vannamei) (WL), black tiger (Penaeus monodon) (BT) and Argentine red (Pleoticus muelleri), and suggested that heads of WL were among the most nutritious source in poultry diets and heads of BT were among the second most nutritious (Rahman and Koh, 2014). Considering the practical use of these SM as a poultry feed ingredient, in vivo data, such as growth performance and feed efficiency, should be needed, but information about them is quite limited (Islam et al, 1994;Oduguwa et al, 2004;Khempaka et al, 2006a;Khempaka et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Diets, Birds and Sampling SM containing 30.4% of chitin was made from headless shells of black tiger shrimp (Penaeus monodon). Details about SM were given in our previous report (Khempaka et al, 2006a). Composition of the experimental diets was given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Ditinjau dari segi kualitas, beberapa penelitian memperlihatkan bahwa limbah udang mengandung protein kasar sebesar 45% -55% (Gernat, 2001;Fanimo et al, 2004;Okaye et al, 2005;Khempaka et al, 2006). Ditinjau dari segi kuantitas, tersedia cukup banyak dan kesinambungannya cukup terjamin karena produksi udang Indonesia setiap tahun selalu mengalami peningkatan.…”
Section: Pendahuluanunclassified
“…Sejauh ini penelitian tentang pemanfaatan limbah udang sebagai pakan ternak telah dilakukan oleh beberapa peneliti terutama untuk pakan unggas (Mirzah, 1990;Supadmo, 1997;Soedibya, 1998;Gernat, 2001;Okaye et al, 2005;Khempaka et al, 2006) dan babi (Fanimo et al, 2004). Namun demikian untuk mendapat gambaran yang lebih jelas tentang taraf penggunaan limbah udang dalam ransum supaya dapat dimanfaatkan pada ternak yang bernilai ekonomi cukup tinggi (ruminansia), maka dilakukan penelitian pendahuluan pada tikus Putih (Rattus norvegicus).…”
Section: Pendahuluanunclassified